Advances in hybrid solar photovoltaic and thermoelectric generators. (May 2017) - Huen, Priscilla; Daoud, Walid A.
Abstract: Development of renewable energies, particularly solar energy, is crucial for meeting future energy needs. Solar light and thermal energy can provide sufficient electricity needed in daily life. In this pursuit, photovoltaics and thermoelectrics have been developing for energy conversion. While photovoltaics mainly convert the UV and visible regions of the solar spectrum, thermoelectrics utilize the IR region. Combining the photovoltaic and thermoelectric effects can extend the effective spectrum range. In recent years, there have been studies on hybrid photovoltaic/thermoelectric systems toward improved conversion efficiency. This review intends to discuss the underlying concepts of photovoltaics and thermoelectrics and summarizes the current research accomplishments and the various approaches used to optimize hybrid photovoltaic/thermoelectric systems. As such, this review encourages further research into hybrid generators due to the promising results achieved. Future prospects and suggestions of potential approaches for further development of these generators are also discussed.